PELATIHAN PEMBUATAN PUPUK KOMPOS SEBAGAI SOLUSI PERMASALAHAN SAMPAH DAUN KERING DI OBJEK WISATA “KALIANGET MANGUNAN” - Sejati, Gentur Ageng (Universitas Wijayakusuma Purwokerto, 2025)
Dry leaf litter is an environmental problem that is often ignored. The accumulation of dry leaves in the surrounding environment can cause various problems such as air pollution and disrupting the aesthetic value of a place. This research aims to identify the problem of dry leaves at the